2020
DOI: 10.1055/a-1274-3675
|View full text |Cite
|
Sign up to set email alerts
|

Real Life Data on Efficacy and Safety of Topical NGF Eye Drops (Cenegermin)

Abstract: Background Topical NGF eye drops (Cenegermin) were approved in 2015 as an orphan drug for the treatment of neurotrophic keratopathy (NK). The active substance Cenegermin is a recombinant form of human NGF (nerve growth factor). Objectives Presentation of efficacy and safety of Cenegermin for use in patients in an university real-life setting. Material and Methods Retrospective study at the Köln University Eye Hospital from 2017 to 2019 with n = 11 eyes. Average follow-up was 13.5 ± 7.1 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
(21 reference statements)
0
6
0
1
Order By: Relevance
“…Additional follow-up data from these studies showed that 87-96% of patients that received 8 weeks of cenegermin treatment remained recurrence free for up to 12 months [6]. Other studies have reported similar results in terms of epithelial healing and long-term recurrence rate [7,[24][25][26].…”
Section: Discussionmentioning
confidence: 76%
“…Additional follow-up data from these studies showed that 87-96% of patients that received 8 weeks of cenegermin treatment remained recurrence free for up to 12 months [6]. Other studies have reported similar results in terms of epithelial healing and long-term recurrence rate [7,[24][25][26].…”
Section: Discussionmentioning
confidence: 76%
“…In the 3 cases of corneal ulcers due to NK treated with cenegermin, reported by Di Zazzo et al [ 22 ], the cause of NK was herpetic keratitis in 2 patients and immune keratitis in one, and all patients healed within 8 weeks therapy with cenegermin. Zwingelberg et al [ 19 ] reported the use of cenegermin in 11 patients with NK stages II and III, with epithelial healing and improvement in vision and corneal sensitivity after 18 months. Bruscolini et al [ 23 ] evaluated 18 patients with NK treated with cenegermin and reported recurrences in 4 patients: within the first 12 months in three and within the first 36 months in one.…”
Section: Discussionmentioning
confidence: 99%
“…Cenegermin is a recombinant human nerve growth factor produced by Escherichia coli that has shown efficacy and safety in promoting healing of corneal ulcers in patients with NK associated with persistent epithelial defects and improvements in other relevant endpoints, such as VA, corneal sensitivity, and disease progression [7]. The efficacy of cenegermin in NK demonstrated in clinical trials [8][9][10] has been confirmed by real-world descriptions of individual cases especially related to the pediatric use of the drug in children with rare congenital diseases [11][12][13][14] as well as in adult patients [15][16][17][18][19][20][21][22][23]. Here, we report the long-term results of 5 adult patients with NK treated successfully with cenegermin and followed for over a period of 4 years after healing of corneal ulcers.…”
Section: Introductionmentioning
confidence: 95%
“…Safety and efficacy of Cenegermin have been evaluated in two double-masked studies, involving 151 patients with NK, restoring corneal integrity in 70% of subjects affected by moderate/ severe NK. 9,10 In 11 eyes affected with NK stage II or III, Zwingelberg et al 11 reported complete epithelial closure within 12 weeks of Cenegermin treatment, with long-term improvements in vision and corneal sensitivity.…”
Section: Discussionmentioning
confidence: 99%